A bridged conductive network enhanced high-activity component SSA electrode, and a preparation process and application thereof

CN122998929APending Publication Date: 2026-10-30QILU ZHONGKE ELECTRICAL ADVANCED ELECTROMAGNETIC DRIVE TECH RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611277821.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]为解决现有技术中SSA电极导电网络连续性不足、非活性组分占比较高以及电荷利用率有待提高等问题,本发明提供一种桥联导电网络增强型高活性组分SSA电极及其制备工艺和应用

Benefits of technology

[0037](1)在组分层面,本发明通过引入桥联导电材料并优化其与活性炭的配比关系,在保证电极结构稳定性的前提下,降低了非活性组分占比,使单位质量电极中活性吸附位点密度显著增加,为提升CO2吸附容量提供了物质基础。本发明的SSA电极中,导电炭黑与桥联导电材料在电极中承担不同尺度、不同机制的导电功能,二者并非替代关系,而是空间尺度上的互补关系;导电炭黑为0维材料,其为点接触,提供短程电子跳跃通道,属于“补缺型”导电剂;桥联导电材料(高长径比纤维/管)为1维材料,为线接触。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998929A_ABST
    Figure CN122998929A_ABST
Patent Text Reader

Abstract

The application discloses a bridged conductive network enhanced high-activity component SSA electrode and a preparation process and application thereof, and belongs to the technical field of electrochemical carbon capture. The bridged conductive network enhanced high-activity component SSA electrode comprises the following components in proportion by weight: active carbon: 80-95 wt%, conductive carbon black: 1-10 wt%, bridged conductive material: 0.1-5 wt%, binder: 1.5-8 wt% and film-forming auxiliary agent: 0.1-3 wt%. By introducing the bridged conductive material and optimizing the ratio relationship between the bridged conductive material and the active carbon, the proportion of non-active components is reduced under the premise of ensuring the stability of the electrode structure, so that the density of active adsorption sites in the unit mass electrode is significantly increased, and a material basis for improving the CO2 adsorption capacity is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical carbon capture technology, and particularly relates to a bridged conductive network enhanced high-activity component SSA electrode, its preparation process, and its application. Background Technology

[0002] With the continuous advancement of global environmental protection goals, carbon dioxide capture, utilization, and storage (CCUS) technology has received widespread attention. Supercapacitive swing adsorption (SSA), as a novel electrochemical carbon dioxide capture technology, possesses advantages such as no need for chemical adsorbents, good cycle performance, relatively low energy consumption, and ease of modular application, showing promising application prospects in the field of electrochemical carbon capture. SSA technology primarily utilizes the electrical double-layer structure formed by the electrode material during charging and discharging to achieve carbon dioxide adsorption and desorption. During charging, the charge density on the electrode surface increases, which is conducive to the enrichment of carbon dioxide at the electrode interface; during discharging, the charge on the electrode surface decreases, releasing the adsorbed carbon dioxide, thus achieving reversible adsorption and desorption of carbon dioxide. The carbon dioxide adsorption capacity, adsorption rate, cycle stability, and energy consumption of the SSA electrode are closely related to factors such as the electrode material composition, conductivity, and pore structure.

[0003] Currently, SSA electrodes typically use activated carbon as the adsorbent, conductive carbon black as the conductive agent, polytetrafluoroethylene (PTFE) as the binder, and film-forming aids such as gluten powder, prepared through processes such as mixing and pressing. Among existing technologies, Chinese patent CN117650015A discloses a supercapacitor swing adsorption carbon capture electrode and its preparation process, using composite activated carbon, conductive carbon black, and PTFE to prepare the electrode, but it does not optimize the conductive network structure; the conductive agent is mainly distributed in particulate form, and the continuity of the electrode's conductive pathway still has room for improvement. Chinese patent CN116328609A discloses a porous carbon electrode preparation process for electrochemical carbon capture, increasing the specific surface area of ​​activated carbon through physical activation, but it does not optimize the content of inactive components; the proportion of conductive agent and binder is relatively high, which has a certain impact on the proportion of active components per unit mass of electrode. The paper “Enhancing Supercapacitive Swing Adsorption of CO2 with Advanced Activated Carbon Electrodes” (Advanced Sustainable Systems, 2023) reports on the performance of traditional SSA electrodes. These electrodes use carbon black particles to construct a conductive network. After the electrodes are compacted, the continuity of the conductive pathway decreases, and the electrode capacity decays significantly under high current density conditions.

[0004] There is still room for further optimization in terms of material composition and conductive structure of existing SSA electrodes.

[0005] On the one hand, existing SSA electrodes typically contain a certain proportion of PTFE binder, gluten powder and other film-forming aids, and conductive carbon black and other inactive components. The PTFE binder content is generally 5–15 wt%, the gluten powder content is generally 2–10 wt%, the conductive carbon black content is generally 3–10 wt%, and the total content of inactive components can typically reach 15–30 wt%. While these inactive components help ensure the mechanical strength and conductivity of the electrode, they do not participate in carbon dioxide adsorption. As their content increases, the proportion of activated carbon per unit mass of electrode decreases accordingly, which may have a certain impact on the electrode's adsorption capacity and electrochemical performance.

[0006] On the other hand, traditional conductive carbon black is mainly dispersed in the electrode in particulate form, and its conductive network relies primarily on the contact between particles to form. When the electrode is pressed into shape, the contact state between particles may change, reducing the continuity of local conductive pathways and increasing the internal resistance of the electrode, thus affecting electron transport efficiency. Simultaneously, due to the limited contact area between activated carbon particles, the electron transport capacity in some areas is relatively weak, potentially affecting the overall charge utilization rate of the electrode. Furthermore, pressing to increase the electrode compaction density may also affect the pore structure and mass transfer process; therefore, it is necessary to comprehensively consider the matching relationship between conductivity, pore structure, and compaction density.

[0007] Therefore, developing an electrode that can improve the continuity of the conductive network, increase charge utilization, and take into account carbon dioxide adsorption performance while maintaining a high content of active components is an urgent technical problem to be solved. Summary of the Invention

[0008] To address the problems of insufficient continuity of conductive network, high proportion of inactive components, and need to improve charge utilization in existing SSA electrodes, this invention provides a bridged conductive network-enhanced high-activity component SSA electrode, its preparation process, and its application.

[0009] This invention employs a bridging conductive material with a high aspect ratio to form continuous conductive connections between activated carbon particles, thereby improving the continuity of the conductive network within the electrode and enhancing electron transport efficiency. Simultaneously, by optimizing the amount of bridging conductive material added and the electrode formulation, the proportion of inactive components in the electrode is reduced, while the proportion of active components per unit mass of electrode is increased. Furthermore, a multi-stage roll forming process is combined to maintain the continuity of the conductive network while preserving a high compaction density, thus improving the electrode's electrochemical performance and carbon dioxide adsorption performance.

[0010] To achieve the above objectives, the present invention adopts the following technical solution:

[0011] A bridged conductive network enhanced high-activity component SSA electrode comprises the following components in parts by weight:

[0012] Activated carbon: 80-95 parts, conductive carbon black: 1-10 parts, bridging conductive material: 0.1-5 parts, binder: 1.5-8 parts, film-forming aid: 0.1-3 parts;

[0013] The mass ratio of activated carbon to bridging conductive material, and the geometric dimensions of the bridging conductive material, satisfy the following relationship:

[0014] ;

[0015] In the relation The weight ratio of the bridging conductive material in the electrode; The weight ratio of activated carbon in the electrode is given by L, where L is the average length of the bridging conductive material and D is the average diameter of the bridging conductive material.

[0016] The composition includes 85-90 parts activated carbon, 0.8-3.5 parts bridging conductive material, 2-7 parts conductive carbon black, 1.5-3.5 parts binder, and 0.2-1.5 parts film-forming aid. More preferably, the activated carbon comprises 87-90 parts, and the bridging conductive material preferably comprises 0.8-1.5 parts.

[0017] The average diameter D of the bridging conductive material is 5–150 nm, and the average length L of the bridging conductive material is 5–50 μm.

[0018] The bridging conductive material is selected from one or more of vapor-grown carbon fibers, carbon nanotubes, carbon nanofibers, and graphene fibers; the carbon nanotubes are at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; the carbon nanofibers are at least one of vapor-grown carbon nanofibers and electrospun carbon nanofibers; the binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, and styrene-butadiene rubber; and the film-forming aid is one or more of gluten powder, starch, polyvinyl alcohol, and polyethylene glycol.

[0019] The activated carbon has a specific surface area of ​​1500–3500 m². 2 / g, pore volume 0.5~2.0cm 3 / g of activated carbon for supercapacitors with an average pore size of 1.0 to 4.0 nm; the median particle size D50 of the activated carbon particles is 5 to 20 μm.

[0020] The fabrication process of the aforementioned bridged conductive network-enhanced highly active component SSA electrode includes the following steps:

[0021] S1: Weigh out activated carbon, conductive carbon black, bridging conductive material, binder and film-forming aid according to the weight ratio;

[0022] S2: Add the bridging conductive material to ethanol and pre-disperse it by ultrasound to obtain a bridging conductive material dispersion;

[0023] S3: Add activated carbon and conductive carbon black to the bridging conductive material dispersion for primary dispersion treatment, so that the bridging conductive material uniformly coats and bridges the activated carbon particles.

[0024] S4: Add the binder and film-forming aid to the dispersion system obtained in step S3 and mix them at low intensity to obtain a slurry. The binder and film-forming aid are evenly distributed in the slurry without destroying the already formed bridging structure.

[0025] S5: Evaporate the dispersion medium of the slurry obtained in step S4 at 40-100℃ to obtain a uniform wet precursor.

[0026] S6: Press the wet precursor into an electrode sheet;

[0027] S7: The electrode sheet is subjected to roll pressing densification treatment;

[0028] S8: The rolled electrode sheet is vacuum dried at 80~120℃ for 6~24 hours to obtain the bridged conductive network enhanced high-activity component SSA electrode.

[0029] In step S3, the main dispersion process employs ball milling dispersion, high-speed shear dispersion, or planetary mixing dispersion.

[0030] The low-intensity mixing in step S4 is carried out using a planetary mixer with a mixing speed of 50-200 rpm and a mixing time of 0.5-2 hours.

[0031] In step S5, evaporation is carried out by water bath heating evaporation or vacuum rotary evaporation.

[0032] The pressing in step S6 is performed by molding or roller pressing, and the pressing pressure is 1 to 10 MPa.

[0033] The total compression rate of the roll densification process in step S7 is 30-70%. The total compression rate refers to the ratio of the thickness reduction of the electrode sheet after roll densification to the original thickness.

[0034] Among them, the roll pressing densification process in step S7 is a multi-stage roll pressing densification process, which specifically includes: the first stage roll pressing pressure is 5 to 20 MPa, and the number of roll pressing times is 1 to 3; the second stage roll pressing pressure is 20 to 50 MPa, and the number of roll pressing times is 2 to 5.

[0035] The application of the aforementioned bridged conductive network enhanced high-activity component SSA electrode in the oscillating adsorption of carbon dioxide in supercapacitors involves assembling the aforementioned bridged conductive network enhanced high-activity component SSA electrode and electrolyte into an SSA carbon capture unit, and realizing the adsorption and desorption of carbon dioxide through charge-discharge cycles.

[0036] The beneficial effects of this invention are as follows:

[0037] (1) At the component level, this invention introduces bridging conductive materials and optimizes their ratio with activated carbon, thereby reducing the proportion of inactive components while ensuring the stability of the electrode structure. This significantly increases the density of active adsorption sites per unit mass of electrode, providing a material basis for improving CO2 adsorption capacity. In the SSA electrode of this invention, conductive carbon black and bridging conductive materials perform conductive functions at different scales and with different mechanisms. They are not substitutes for each other, but rather complementary in terms of spatial scale. Conductive carbon black is a 0-dimensional material, providing point contact and short-range electron hopping channels, and is a "gap-filling" conductive agent. The bridging conductive material (high aspect ratio fiber / tube) is a 1-dimensional material, providing line contact.

[0038] (2) In terms of conductivity mechanism, unlike traditional particle contact conductivity, this invention uses high aspect ratio bridging materials to form a continuous conductive connection between activated carbon particles, which significantly improves the electron transport path, effectively reduces the internal resistance of the electrode, and thus improves charge utilization and electrochemical response speed.

[0039] (3) In terms of process synergy, the present invention combines the bridging conductive network with the multi-stage rolling densification process, so that the electrode can maintain the continuity and structural integrity of the conductive network under high compaction density, overcoming the contradiction of channel collapse and conductivity deterioration caused by high compaction of traditional electrodes, and achieving a balance between conductivity and mass transfer performance.

[0040] (4) In terms of application and industrialization, the SSA electrode obtained by this invention has excellent performance in CO2 adsorption capacity and adsorption rate, which can meet the performance requirements of supercapacitor swing adsorption carbon capture technology; and the preparation process is based on conventional mixing, pressing and rolling equipment, with a wide operating window, controllable parameters and good reproducibility, and has good prospects for industrial promotion. Attached Figure Description

[0041] Figure 1 The image shows a scanning electron microscope (SEM) image of the bridged conductive network-enhanced high-activity component SSA electrode prepared in Example 1.

[0042] Figure 2 SEM image of the electrode prepared for Comparative Example 1.

[0043] Figure 3 The image shows a SEM image of the electrode prepared in Example 3.

[0044] Figure 4 The curves showing the change in carbon dioxide concentration with charge / discharge voltage for the bridged conductive network-enhanced highly active component SSA electrode prepared in Example 1 during carbon dioxide adsorption capacity testing.

[0045] Figure 5The curve showing the change of carbon dioxide concentration with charge / discharge voltage when the electrode prepared for Comparative Example 1 is used in the carbon dioxide adsorption capacity test.

[0046] Figure 6 These are impedance test results of the electrodes prepared in Examples 1 to 3 and Comparative Example 1. Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0048] In the following embodiments and comparative examples, unless otherwise stated, the test methods and evaluation metrics used are as follows:

[0049] (1) Impedance test: The test was conducted using an electrochemical workstation.

[0050] (2) Specific capacitance test: A three-electrode system was used, with the prepared electrode sheet as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. The electrolyte was a 1 mol / L Na2SO4 aqueous solution. Constant current charge-discharge tests were performed on an electrochemical workstation with a current density of 0.05 A / g (based on the mass of activated carbon) and a potential window of 0–1 V. The specific capacitance was calculated using the formula C = I·Δt / (m·ΔV), where I is the discharge current, Δt is the discharge time, m is the mass of activated carbon, and ΔV is the potential window.

[0051] (3) Carbon dioxide adsorption capacity test: The electrode sheet and electrolyte (1 mol / L Na2SO4) were assembled into a symmetrical SSA test unit, and a mixed gas (15% CO2, 85% N2, flow rate 1 sccm, temperature 25℃) was introduced. The carbon dioxide concentration change under different charge and discharge voltages was monitored in real time by an in-situ electrochemical mass spectrometer.

[0052] Example 1:

[0053] This embodiment provides a bridged conductive network-enhanced highly active component SSA electrode, the fabrication process of which includes the following steps:

[0054] S1. Weigh each component according to the formula. Among them, coconut shell-based supercapacitor activated carbon (specific surface area 2100 m²) 2 / g, pore volume 1.2 cm 3 / g, average pore size 2.1 nm, D 5089 wt% of the following: conductive carbon black (Super P C45) (12 μm); 5 wt% of the following: vapor-grown carbon fiber (VGCF, average diameter 150 nm, average length 15 μm, aspect ratio approximately 100); 1.5 wt% of the following: polytetrafluoroethylene (PTFE) aqueous dispersion (60% solids content, equivalent to approximately 3.5 wt% PTFE dry basis); and 1 wt% of the following: wheat gluten powder.

[0055] S2: VGCF is added to anhydrous ethanol and pre-dispersed by ultrasound to obtain a bridging conductive material dispersion.

[0056] S3: Add activated carbon and conductive carbon black to the bridging conductive material dispersion obtained in step S2, and disperse it by ball milling in a planetary ball mill with a ball-to-material ratio of 5:1, a ball milling speed of 400 rpm, and a ball milling time of 6 h, so that the bridging conductive material is uniformly dispersed between the activated carbon particles.

[0057] S4: Add PTFE aqueous dispersion and gluten powder to the mixture obtained in step S3, and stir at 120 rpm for 1 h to ensure uniform distribution of binder and film-forming aid.

[0058] S5: Heat the slurry obtained in step S4 in an 80 ℃ water bath to evaporate the ethanol and obtain a wet precursor.

[0059] S6: The wet precursor is pre-pressed by molding, with a pre-pressing pressure of 5 MPa and a holding time of 2 min, to obtain an electrode sheet with a diameter of 20 mm.

[0060] S7: The electrode sheet undergoes multi-stage rolling processing. This multi-stage rolling process includes three stages: the first stage has a rolling pressure of 15 MPa and is performed twice; the second stage has a rolling pressure of 35 MPa and is performed three times; the total compression rate is approximately 50%.

[0061] S8: The rolled electrode sheet was dried in a vacuum drying oven at 100 ℃ for 12 h to obtain a bridged conductive network-enhanced high-activity component SSA electrode. The resulting electrode had a thickness of approximately 0.4 mm and an areal density of approximately 12 mg / cm³. 2 .

[0062] The mass ratio of activated carbon to bridging conductive material and the relationship between the geometric dimensions of the bridging conductive material in Example 1 are as follows:

[0063] 0.0778.

[0064] Example 2:

[0065] This embodiment is basically the same as Embodiment 1, except that the amount of VGCF bridging conductive material added is adjusted to 0.8 wt%, the activated carbon content is adjusted to 89.7 wt%, and the remaining preparation steps are the same as in Embodiment 1.

[0066] The mass ratio of activated carbon to bridging conductive material and the relationship between the geometric dimensions of the bridging conductive material in Example 2 are as follows:

[0067] 0.0411.

[0068] Example 3:

[0069] The difference between this embodiment and Example 1 is that the amount of VGCF added is adjusted to 3.5wt%, activated carbon to 87wt%, conductive carbon black to 5wt%, PTFE dry basis to 3.5wt%, and gluten powder to 1.0wt%.

[0070] The mass ratio of activated carbon to bridging conductive material and the relationship between the geometric dimensions of the bridging conductive material in Example 3 are as follows:

[0071] 0.185.

[0072] Example 4:

[0073] The difference between this embodiment and Embodiment 1 is that the bridging conductive material is replaced by multi-walled carbon nanotubes (MWCNTs, average diameter 20nm, average length 10μm, aspect ratio 500) with an addition amount of 0.8wt%, activated carbon is adjusted to 89.7wt%, conductive carbon black is adjusted to 5wt%, PTFE dry basis is adjusted to 3.5wt%, and gluten powder is adjusted to 1.0wt%.

[0074] The mass ratio of activated carbon to bridging conductive material and the relationship between the geometric dimensions of the bridging conductive material in Example 4 are as follows:

[0075] 0.0554.

[0076] Example 5:

[0077] The only difference between this embodiment and Example 1 is the ball milling and dispersion parameters in step S3: the ball-to-material mass ratio is 3:1, the ball milling speed is 300 rpm, and the ball milling time is 4 hours. All other components, contents, and preparation steps are the same as in Example 1.

[0078] Example 6:

[0079] The only difference between this embodiment and Example 1 is the ball milling and dispersion parameters in step S3: the ball-to-material mass ratio is 10:1, the ball milling speed is 500 rpm, and the ball milling time is 8 hours. All other components, contents, and preparation steps are the same as in Example 1.

[0080] Example 7:

[0081] The only difference between this embodiment and Example 1 is the low-intensity mixing parameters in step S4: the planetary stirrer rotates at 50 rpm for 0.5 h. All other components, contents, and preparation steps are the same as in Example 1.

[0082] Example 8:

[0083] The only difference between this embodiment and Example 1 is the low-intensity mixing parameters in step S4: the planetary stirrer rotates at 200 rpm for 2 hours. All other components, contents, and preparation steps are the same as in Example 1.

[0084] Example 9:

[0085] The only difference between this embodiment and Example 1 is the evaporation temperature in step S5: the water bath heating temperature is 40°C. All other components, contents, and preparation steps are the same as in Example 1.

[0086] Example 10:

[0087] The only difference between this embodiment and Example 1 is the evaporation temperature in step S5: the water bath heating temperature is 100°C. All other components, contents, and preparation steps are the same as in Example 1.

[0088] Example 11:

[0089] The only difference between this embodiment and Example 1 is the multi-stage rolling parameters in step S7: the first-stage rolling pressure is 5 MPa, and the rolling is performed once; the second-stage rolling pressure is 20 MPa, and the rolling is performed twice, with a total compression rate of approximately 30%. The remaining components, contents, and other preparation steps are the same as in Example 1.

[0090] Example 12:

[0091] The only difference between this embodiment and Example 1 is the multi-stage rolling parameters in step S7: the first-stage rolling pressure is 20 MPa, and the rolling is performed 3 times; the second-stage rolling pressure is 50 MPa, and the rolling is performed 5 times, with a total compression rate of approximately 70%. The remaining components, contents, and other preparation steps are the same as in Example 1.

[0092] Comparative example:

[0093] Comparative Example 1 (non-bridging conductive material):

[0094] The difference between this comparative example and Example 1 is that no bridging conductive material is added, the activated carbon content is adjusted to 89 wt%, the conductive carbon black content is adjusted to 6.5 wt% (to maintain the total conductive agent content the same as the total amount of conductive carbon black + VGCF in Example 1, both being 6.5 wt%), the PTFE dry basis is 3.5 wt%, and the gluten powder is 1.0 wt%. In the preparation process, the dispersion of bridging materials in steps S2 and S3 is omitted. The activated carbon and conductive carbon black are directly mixed with PTFE and gluten powder in anhydrous ethanol by planetary stirring for 2 hours. The remaining pressing, rolling, and drying steps are the same as in Example 1.

[0095] Comparative Example 2 (Single-stage high-pressure pressing replacing multi-stage roller pressing):

[0096] The formulation of this comparative example is exactly the same as that of Example 1, but step S7 is changed to single-stage rolling: the pressure is 50 MPa, the rolling is performed 5 times, and the total compression ratio is about 50% (the same as the total compression ratio of Example 1). The rest of the preparation process is the same as that of Example 1.

[0097] Figure 1 The image shows a scanning electron microscope (SEM) image of the bridged conductive network-enhanced high-activity component SSA electrode prepared in Example 1. Figure 2 SEM image of the electrode prepared for Comparative Example 1. Figure 3 The image shows a SEM image of the electrode prepared in Example 3. Figure 1 The SEM images show that the bridging conductive material in the SSA electrode prepared in this invention forms a three-dimensional bridging structure between activated carbon particles. Figure 2 The SEM image (Comparative Example 1) shows that the conductive carbon black in the electrode without the addition of bridging conductive material is dispersed in particulate form and does not form a continuous bridging network. Figure 3 The SEM image (Example 3) shows that the bridging conductive material is unevenly distributed, with agglomeration and bridging fracture areas.

[0098] Performance test results:

[0099] The performance test results of Examples 1-12 and Comparative Examples 1-2 are summarized in Table 1.

[0100] Table 1. Comparison of electrode performance between each embodiment and the comparative example

[0101]

[0102] Results analysis:

[0103] (1) The effect of introducing bridging conductive materials.

[0104] Comparative Example 1 uses a traditional conductive carbon black system without adding any bridging conductive material. Test results show that Comparative Example 1 has a specific capacitance of 80 F / g and a sheet resistivity of 0.100 Ω·cm.2 The carbon dioxide adsorption capacity was 68.38 mmol / kg, and the adsorption rate was 67.70 μmol·kg⁻¹. -1 ·s -1 .

[0105] Example 1 uses VGCF as the bridging conductive material. Under essentially the same conditions, the specific capacitance is increased to 156 F / g, and the sheet resistivity is reduced to 0.020 Ω·cm. 2 The carbon dioxide adsorption capacity increased to 151.96 mmol / kg, and the adsorption rate increased to 150.46 μmol·kg⁻¹. -1 ·s -1 . Figure 4 The curve showing the change of carbon dioxide concentration with charge / discharge voltage during the carbon dioxide adsorption capacity test of the electrode in Example 1 is shown. Figure 5 The curves showing the carbon dioxide concentration versus charge / discharge voltage for the electrode of Comparative Example 1 under the same test conditions are presented. Figure 4 and Figure 5 It can be seen that, under the same current density (50 mA / g), the adsorption concentration of carbon dioxide decreased from the highest point of 33.7% to the lowest point of 4.54% in the test using the electrode of Example 1, while the adsorption concentration of carbon dioxide decreased from the highest point of 22.38% to the lowest point of 5.62% in the test using the electrode of Comparative Example 1, with a more significant change in concentration.

[0106] As shown in Table 1, the introduction of the bridging conductive material improves the electrode's specific capacitance, reduces its surface resistivity, and enhances both the carbon dioxide adsorption capacity and adsorption rate. This indicates that the bridging conductive material helps improve the internal conductive network of the electrode, increasing electron transport efficiency and thus enhancing the overall performance of the SSA electrode. Furthermore, without the bridging conductive material, the point contact of the conductive carbon black is easily interrupted after compaction.

[0107] (2) Verification of the relation.

[0108] Examples 1, 2, and 3 used different amounts of VGCF, and their corresponding calculated values ​​were 0.0778, 0.0411, and 0.185, respectively. Test results showed that the carbon dioxide adsorption capacities of the three examples were 151.96 mmol / kg, 140.56 mmol / kg, and 128.90 mmol / kg, respectively, and their surface resistivity was 0.020 Ω·cm. 2 0.060 Ω·cm 2 and 0.058 Ω·cm 2The overall performance of the electrodes in Example 1 was superior to that of Comparative Example 1, which did not contain bridging conductive material. Specifically, the electrode in Example 1 exhibited lower sheet resistance and higher carbon dioxide adsorption capacity. In Example 2, as the amount of bridging conductive material added decreased, the electrode sheet resistance increased, while the carbon dioxide adsorption capacity decreased. In Example 3, further increasing the amount of bridging conductive material did not further reduce the electrode sheet resistance, but the carbon dioxide adsorption capacity decreased, indicating that the amount of bridging conductive material added has a certain impact on the overall performance of the electrode.

[0109] Figure 6 These are impedance test results for the electrodes prepared in Examples 1 to 3 and Comparative Example 1. From... Figure 6 It can be seen that the impedance arc radius (Rct value) of Example 1 is significantly smaller than that of Example 3 and Comparative Example 1, indicating that the interface impedance of Example 1 is relatively low and the electron transport performance is good. This result is basically consistent with the surface resistance test results.

[0110] The test results from Examples 1-3 show that, within the range of the relationships described in this invention, variations in the amount of bridging conductive material added affect the electrode's conductivity and carbon dioxide adsorption performance. By rationally controlling the amount of bridging conductive material added, it is beneficial to obtain an SSA electrode with better overall performance.

[0111] (3) The influence of the type of bridging conductive material.

[0112] Example 4 used multi-walled carbon nanotubes (MWCNTs, aspect ratio approximately 500) as the bridging conductive material, while Example 2 used VGCF (aspect ratio approximately 100) as the bridging conductive material. Under the conditions of the same amount of bridging conductive material and similar product values ​​in the relational formula, Example 4 showed a carbon dioxide adsorption capacity of 144.36 mmol / kg and a sheet resistivity of 0.025 Ω·cm. 2 The carbon dioxide adsorption capacity of Example 2 was 140.56 mmol / kg, and the surface resistivity was 0.060 Ω·cm. 2 .

[0113] The test results show that, under the same addition conditions, using a bridging conductive material with a higher aspect ratio results in a lower electrode surface resistance and a higher carbon dioxide adsorption capacity. This indicates that the aspect ratio of the bridging conductive material has a certain impact on the electrode's conductivity and carbon dioxide adsorption performance. Under the conditions of this invention, appropriately increasing the aspect ratio of the bridging conductive material is beneficial for further improving the overall electrode performance.

[0114] (4) The influence of ball milling dispersion conditions.

[0115] Example 5 used a ball-to-material ratio of 3:1, a ball milling speed of 300 rpm, and a ball milling time of 4 h; Example 6 used a ball-to-material ratio of 10:1, a ball milling speed of 500 rpm, and a ball milling time of 8 h, with all other preparation conditions being the same as in Example 1.

[0116] The test results show that the carbon dioxide adsorption capacity of Example 5 is 134.64 mmol / kg, and the surface resistivity is 0.035 Ω·cm. 2 The carbon dioxide adsorption capacity of Example 6 was 143.45 mmol / kg, and the surface resistivity was 0.028 Ω·cm. 2 The carbon dioxide adsorption capacity of Example 1 was 151.96 mmol / kg, and the surface resistivity was 0.020 Ω·cm. 2 .

[0117] The results above show that ball milling dispersion conditions have a certain impact on electrode performance. Under the conditions of this invention, the electrode prepared using the ball milling parameters in Example 1 has a lower sheet resistance and a higher carbon dioxide adsorption capacity, indicating that using appropriate ball milling dispersion conditions is beneficial to the dispersion of bridging conductive materials and helps to improve the overall performance of the electrode.

[0118] (5) The effect of low-intensity mixing conditions.

[0119] Example 7 used a stirring speed of 50 rpm and a stirring time of 0.5 h; Example 8 used a stirring speed of 200 rpm and a stirring time of 2 h, and the other preparation conditions were the same as those in Example 1.

[0120] The test results show that the carbon dioxide adsorption capacities of Examples 7, 8, and 1 are 145.27 mmol / kg, 149.12 mmol / kg, and 151.96 mmol / kg, respectively, and the surface resistivity is 0.026 Ω·cm. 2 0.022 Ω·cm 2 and 0.020 Ω·cm 2 The performance differences between the various embodiments are small.

[0121] The results above show that, within the range of stirring speed and stirring time described in this invention, low-intensity mixing conditions have little impact on electrode performance, and SSA electrodes with good conductivity and carbon dioxide adsorption performance can be obtained, indicating that the above process parameters have a certain range of applicability.

[0122] (6) The effect of evaporation temperature.

[0123] In Example 9, evaporation was carried out at 40 °C, and in Example 10, evaporation was carried out at 100 °C. All other preparation conditions were the same as in Example 1.

[0124] The test results show that the carbon dioxide adsorption capacities of Examples 9, 10, and 1 are 150.25 mmol / kg, 147.20 mmol / kg, and 151.96 mmol / kg, respectively, and the surface resistivity is 0.019 Ω·cm. 2 0.024 Ω·cm 2 and 0.020 Ω·cm 2 .

[0125] The results above show that within the evaporation temperature range of 40–100 °C, the differences in carbon dioxide adsorption capacity and surface resistivity of the electrodes obtained in each embodiment are small, indicating that the evaporation temperature has a relatively small impact on the overall performance of the electrodes. Among them, the electrode obtained at the evaporation temperature used in Example 1 has better overall performance and can be considered as a preferred embodiment of the present invention.

[0126] (7) Optimization of multi-stage rolling conditions.

[0127] Example 11 used a total compression ratio of 30%, Example 12 used a total compression ratio of 70%, and Example 1 used a total compression ratio of 50%. All other preparation conditions were the same.

[0128] The test results show that the carbon dioxide adsorption capacities of Examples 11, 12, and 1 are 144.36 mmol / kg, 136.68 mmol / kg, and 151.96 mmol / kg, respectively, and the surface resistivity is 0.032 Ω·cm. 2 0.040 Ω·cm 2 and 0.020 Ω·cm 2 .

[0129] The results above show that different total compression ratios have a certain impact on electrode performance. Under the conditions of this invention, the electrode obtained by the total compression ratio used in Example 1 has lower sheet resistance and higher carbon dioxide adsorption capacity, indicating that appropriately controlling the rolling compression ratio is beneficial to improving the overall performance of the electrode.

[0130] To further compare the effects of different rolling methods, under the same total compression ratio, Comparative Example 2 used single-stage high-pressure rolling, while Example 1 used multi-stage rolling. Test results showed that the sheet resistivity of Comparative Example 2 was 0.065 Ω·cm. 2 The carbon dioxide adsorption capacity was 112.30 mmol / kg; the surface resistivity of Example 1 was 0.020 Ω·cm. 2 The carbon dioxide adsorption capacity is 151.96 mmol / kg.

[0131] The results above show that, under the same total compression ratio, the electrode obtained by multi-stage rolling has a lower sheet resistance and a higher carbon dioxide adsorption capacity, indicating that the multi-stage rolling method is beneficial to improving the electrode's conductivity and carbon dioxide adsorption performance, and can be used as a preferred embodiment of the present invention.

[0132] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention. The above embodiments are provided only for the purpose of describing the present invention and are not intended to limit the present invention. Parts not described in detail in this specification are well-known in the art and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. All equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be covered within the scope of the present invention.

Claims

1. A bridged conductive network-enhanced high-activity component SSA electrode, characterized in that, The bridged conductive network enhanced high-activity component SSA electrode comprises the following components in parts by weight: Activated carbon: 80-95 parts, conductive carbon black: 1-10 parts, bridging conductive material: 0.1-5 parts, binder: 1.5-8 parts, film-forming aid: 0.1-3 parts; The mass ratio of activated carbon to bridging conductive material, and the geometric dimensions of the bridging conductive material, satisfy the following relationship: ; In the relation The weight ratio of the bridging conductive material in the electrode; The weight ratio of activated carbon in the electrode is given by L, where L is the average length of the bridging conductive material and D is the average diameter of the bridging conductive material.

2. The bridged conductive network enhanced high-activity component SSA electrode according to claim 1, characterized in that, The active carbon content is 85-90 parts, the bridging conductive material content is 0.8-3.5 parts, the conductive carbon black content is 2-7 parts, the binder content is 1.5-3.5 parts, and the film-forming aid content is 0.2-1.5 parts.

3. The bridged conductive network enhanced high-activity component SSA electrode according to claim 1, characterized in that, The average diameter D of the bridging conductive material is 5–150 nm, and the average length L of the bridging conductive material is 5–50 μm.

4. The bridged conductive network enhanced high-activity component SSA electrode according to claim 1, characterized in that, The bridging conductive material is selected from one or more of vapor-grown carbon fibers, carbon nanotubes, carbon nanofibers, and graphene fibers; wherein the carbon nanotubes are at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes; the carbon nanofibers are at least one of vapor-grown carbon nanofibers and electrospun carbon nanofibers; the binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, and styrene-butadiene rubber; and the film-forming aid is one or more of gluten powder, starch, polyvinyl alcohol, and polyethylene glycol.

5. The bridged conductive network enhanced high-activity component SSA electrode according to claim 1, characterized in that, The activated carbon has a specific surface area of ​​1500–3500 m². 2 / g, pore volume 0.5~2.0cm 3 / g of activated carbon for supercapacitors with an average pore size of 1.0 to 4.0 nm; the median particle size D50 of the activated carbon particles is 5 to 20 μm.

6. The fabrication process of the bridged conductive network enhanced high-activity component SSA electrode according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Weigh out activated carbon, conductive carbon black, bridging conductive material, binder and film-forming aid according to the weight ratio; S2: Add the bridging conductive material to ethanol and pre-disperse it by ultrasound to obtain a bridging conductive material dispersion; S3: Add activated carbon and conductive carbon black to the bridging conductive material dispersion liquid for primary dispersion treatment, so that the bridging conductive material uniformly coats and bridges the activated carbon particles. S4: Add the binder and film-forming aid to the dispersion system obtained in step S3 and mix them at low intensity to obtain a slurry. The binder and film-forming aid are evenly distributed in the slurry without destroying the already formed bridging structure. S5: Evaporate the dispersion medium of the slurry obtained in step S4 at 40-100℃ to obtain a uniform wet precursor. S6: Press the wet precursor into an electrode sheet; S7: The electrode sheet is subjected to roll pressing densification treatment; S8: The rolled electrode sheet is vacuum dried at 80~120℃ for 6~24 hours to obtain the bridged conductive network enhanced high-activity component SSA electrode.

7. The fabrication process of the bridged conductive network-enhanced high-activity component SSA electrode according to claim 6, characterized in that, The main dispersion process in step S3 employs ball milling dispersion, high-speed shear dispersion, or planetary mixing dispersion. The low-intensity mixing in step S4 is carried out using a planetary mixer with a mixing speed of 50-200 rpm and a mixing time of 0.5-2 hours.

8. The fabrication process of the bridged conductive network-enhanced high-activity component SSA electrode according to claim 6, characterized in that, The evaporation in step S5 is performed using water bath heating evaporation or vacuum rotary evaporation; The pressing in step S6 is performed by molding or roller pressing, and the pressing pressure is 1 to 10 MPa. The total compression rate of the roll densification process in step S7 is 30-70%.

9. The fabrication process of the bridged conductive network enhanced high-activity component SSA electrode according to claim 6, characterized in that, The roll pressing densification process in step S7 is a multi-stage roll pressing densification process, which specifically includes: the first stage roll pressing pressure is 5 to 20 MPa, and the number of roll pressing cycles is 1 to 3; the second stage roll pressing pressure is 20 to 50 MPa, and the number of roll pressing cycles is 2 to 5.

10. The application of the bridged conductive network-enhanced highly active component SSA electrode according to any one of claims 1 to 5 in the oscillating adsorption of carbon dioxide in a supercapacitor, characterized in that, The SSA electrode with bridged conductive network enhancement and high activity component as described in any one of claims 1 to 5 and the electrolyte are assembled into an SSA carbon capture unit, and carbon dioxide adsorption and desorption are achieved through charge-discharge cycles.

Citation Information

Patent Citations

  • Vacuum emulsification device and use method thereof

    CN116328609A

  • Application of composite material as active material of positive electrode and super-capacitor carbon dioxide adsorption energy storage device

    CN117650015A